Children's Oncology Group's 2013 blueprint for research: Renal tumors - Dome, Jeffrey S.; Fernandez, Conrad V.; Mullen, Elizabeth A.; Kalapurakal, John A.; Geller, James I.; Huff, Vicki; Gratias, Eric J.; Dix, David B.; Ehrlich, Peter F.; Khanna, Geetika; Malogolowkin, Marcio H.; Anderson, James R.; et al. (Pediatric blood & cancer, 2013)
Renal malignancies are among the most prevalent pediatric cancers. The most common is favorable histology Wilms tumor (FHWT), which has 5‐year overall survival exceeding 90%. Other pediatric renal malignancies, including anaplastic Wilms tumor, clear cell sarcoma, malignant rhabdoid tumor, and renal cell carcinoma, have less favorable outcomes. Recent clinical trials have identified gain of chromosome 1q as a prognostic marker for FHWT. Upcoming studies will evaluate therapy adjustments based on this and other novel biomarkers. For high‐risk renal tumors, new treatment regimens will incorporate biological therapies. A research blueprint, viewed from the perspective of the Children's Oncology Group, is presented. Pediatr Blood Cancer 2013; 60: 994–1000. © 2012 Wiley Periodicals, Inc.